사실혼배우자의 상속권 보장 방법에 관한 一考 - 임영수(Lim, Yeong-Su) (Tonga pŏphak, 2011)
우리나라에서 사실혼배우자에 대한 상속권 보장 여부는 대법원 판결 이후 어느 정도 그 방향에 대한 정리가 이루어졌다고 볼 수 있다. 판례는 사실혼관계가 일방 당사자의 사망으로 종료되는 경우에 생존한 상대방에게는 상속권도 인정되지 않고, 재산분할청구권도 인정되지 않는 것은 사실혼보호라는 관점에서 문제가 있다고 볼 수 있으나, 이는 사실혼배우자를 상속인에 포함시키지 않는 우리 법제에 기인한 것으로서 입법론은 별론으로 하고, 해석론으로서는 어쩔 수 없다는 입장이다. 그러면서 대법원은 위 판례를 통해 사실혼당사자 일방이 사망한 경우 현행법으로는 생존 사실혼배우자를 전혀 보호할 수 없음을 지적하고, 그 해결방향으로 상속권의 인정 등과 같은 입법론적 해결방안을 촉구하고 있다. 그러나 이와 같은 법원의 태도는 사실혼이 생전해소 되는 경우에만 재산관계의 청산을 허용한다는 것으로써 사인해소에 따른 생존 사실혼배우자의 보호에 형평성을 상실한 것이라는 지적을 받고 있다. 이에 따라 생존 사실혼배우자에 대한 형평성 있는 보호방안의 모색이 당면 과제가 되었다. 따라서 현재와 같은 법적 공백을 최소화 시킬 수 있는 방안으로는 사실혼배우자에게 상속권을 인정하는 것이 바람직하다고 본다. 그러나 생존 사실혼배우자에게 상속권을 인정하기 위해서는 상속과 관련된 이해관계인들이 상속인이라는 것을 인식할 수 있어야 한다. 이를 위해서는 어떻게 사실혼배우자라는 것을 입증하고, 어떠한 법리로서 상속권을 취득하고 행사할 수 있는지, 그리고 한계는 없는지 검토해 보아야 한다. 본고는 이와 관련한 내용을 검토하고, 그 방안에 관한 방법론을 제시하였다. It could be said that whether the inheritance of the spouses of a De Factor marriage should be protected was clarified by the ruling of the Supreme Court. The precedent determines that the if the marriage was terminated while both of the spouses were alive, the claim for a partition of the property right could be granted, while when the marriage was terminated by the decease of either spouse, the living spouse cannot be granted with the claim for a partition of the property right but only with the right for inheritance of the properties of the deceased. In this regard, the Supreme Court ruled that, when the De Facto marriage was terminated by decease of one of the spouses, the right for the partition of the property count not be granted to the living one. Further, the precedent also determined that if both of the right of inheritance of the properties of the deceased and the right for the partition of the property were not to be granted, it could be against the law’s intent of protecting the relationship based on a De Facto marriage. But, this is due to our legal system which does not include a spouse in a De Facto marriage as a successor, and there was nothing that could be done in terms of the interpretation of the law, while the perspective of law making was a separate issue. Meanwhile, the Supreme Court also pointed out that the current law provides no protection to the spouse in a De Facto marriage and called for a solution in the perspective of law making. But, such attitude of the court means that the settlement of the property ownership could only be made when the De Facto marriage was terminated while both of the spouses are alive, and it is under the criticism that such an attitude is an injustice in terms of the protection of the spouses in the De Facto marriages. Therefore, it is an imminent issue to be addressed to find a way to provide a balanced protection to such spouses. KCI Citation Count: 5